2002
DOI: 10.1002/bies.10038
|View full text |Cite
|
Sign up to set email alerts
|

Histone ubiquitination: a tagging tail unfolds?

Abstract: Despite the fact that histone H2A ubiquitination affects about 10-15% of this histone in most eukaryotic cells, histone ubiquitination is among one of the less-well-characterized post-translational histone modifications. Nevertheless, some important observations have been made in recent years. Whilst several enzymes had been known to ubiquitinate histones in vitro, recent studies in yeast have led to the unequivocal identification of the enzyme responsible for this post-translational modification in this organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 86 publications
1
105
0
2
Order By: Relevance
“…Disruption of histone Ubiquitinylation is known to lead to defects in DNA repair (Robzyk et al, 2000). The roles that have been proposed for histone Ub are, however, multiple and complex, extending from chromatin uncoiling and gene transcription to gene silencing (Sun and Allis, 2002), and remain controversial (Jason et al, 2002).…”
Section: Dna Repairmentioning
confidence: 99%
“…Disruption of histone Ubiquitinylation is known to lead to defects in DNA repair (Robzyk et al, 2000). The roles that have been proposed for histone Ub are, however, multiple and complex, extending from chromatin uncoiling and gene transcription to gene silencing (Sun and Allis, 2002), and remain controversial (Jason et al, 2002).…”
Section: Dna Repairmentioning
confidence: 99%
“…Covalent modification can occur at both the DNA and histone levels. With histones, modifications include acetylation, phosphorylation, methylation, ubiquitination, and many others (for reviews, see Spencer and Davie, 1999;Strahl and Allis, 2000;Berger, 2002;Jason et al, 2002;Kouzarides, 2007). Different modifications interplay with each other and contribute significantly to the formation of a complex epigenetic program for generating and preserving the defined chromatin state of a given cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Some early studies suggested the involvement of H2A ubiquitylation in gene activation (for review, see Jason et al 2002); however, recent studies have indicated a role for H2A ubiquitylation in gene repression (for reviews, see Zhang 2003;Shilatifard 2006). An H2A ubiquitin ligase was identified, and its complex has been suggested to play a role in Polycomb group (PcG) protein-mediated gene silencing by H2A ubiquitylation (Wang et al 2004).…”
mentioning
confidence: 99%